The Effectiveness of Baby Swimming in Supporting Motor Development of Babies Aged 6-9 Months in Siak Hulu District in 2025 - Sartika, Wiwi; Sara Herlina; Siti Qomariah (Jurnal Maternitas Kebidanan, 2025)
Introduction Motor development in children aged 6-9 months needs to be considered. If stimulation of child growth and development is not carried out, there will be deviations in growth and development that can be delayed in babies. Baby swim is a baby care by swimming in a warm pool with a temperature of 38 to 40 degrees using a float. The function of baby swimming itself is to train body functions, stimulate activity in the baby's muscles safely train the baby's motor system. The purpose of this study is the Effectiveness of Baby Swimming in Supporting Motor Development in Babies Aged 6-9 Months. This research method uses a quasi-experimental with a one group pre-test post-test research design. The sample in this study was babies aged 6-9 months, the sample size used in the study was 30 babies. Data collection was carried out by conducting observations and questionnaires that had been tested for validity and reliability. The results of the study stated that the effectiveness of baby swimming in stimulating gross motor skills in babies aged 6-9 months obtained ap value of 0.000. So it can be concluded that there is effectiveness of baby gym in stimulating gross motor skills in babies aged 6-9 months.